On-line identification of non-linear hysteretic structural systems using a variable trace approach. - Lin, Jeng-Wen (Earthquake engineering & structural dynamics.)
In this paper, an adaptive on-line parametric identification algorithm based on the variable trace approach is presented for the identification of non-linear hysteretic structures. At each time step, this recursive least square based algorithm upgrades the diagonal elements of the adaptation gain matrix by comparing the values of estimated parameters between two consecutive time steps. Such an approach will enforce a smooth convergence of the parameter values, a fast tracking of the parameter changes and will remain adaptive as time progresses. The effectiveness and efficiency of the proposed algorithm is shown by considering the effects of excitation amplitude, of the measurement units of larger sampling time interval and of measurement noise. The cases of exact, under, over parameterization of the structural model have been analysed. The proposed algorithm is also quite effective in identifying time varying structural parameters to simulate cumulative damage in structural systems.